System for Storing, Recovering, and Comparing Gene Expression Information from Patients with Endometriosis - Virginio Junior, Luiz Aparecido; Meola, Juliana; Dentillo, Daniel Blasioli; Rosa e Silva, Júlio César; Ferriani, Rui Alberto; Giuliatti, Silvana (Journal of Health Informatics, 2015)
Objective: To develop a web-based system to store, recover, compare, and associate information obtained using high-throughput molecular genetic techniques regarding differentially expressed genes in patients with endometriosis. Methods: A web-based tool was developed using the Java programming and XHTML markup languages. Professionals and researchers in the field contributed to the database by uploading research data from scientific articles in which screening techniques had been performed to determine differential gene expression in women with and without endometriosis. Results: a web-based system with the main functionalities of article registration and gene searching was developed. These functions allow the user to identify coincidences between the results reported in the registered articles regarding differential gene expression. Conclusion: The developed tool allows for the collection of principal data regarding dysregulated gene expression in endometriosis and highlights candidate genes for future studies to better understand the etiopathogenesis of this disease.